Efficacy comparison of four different Chinese herbal mediciness in intervening acute respiratory distress syndrome: a bayesian network meta-analysis - Wu, Xinhui; Feng, Sisi; Dai, Xuemei; Liu, Zhihao; Luo, Yi; Wang, Fei (Frontiers in Pharmacology, 2025)
BackgroundAcute Respiratory Distress Syndrome (ARDS) is a critical condition with high ICU mortality. Despite treatments such as mechanical ventilation, outcomes remain poor, with in-hospital mortality reaching 40% and various complications negatively affecting patient prognosis. Chinese Herbal Medicines (CHM) offers a promising, safe, and reliable alternative therapy. When combined with Western symptomatic treatments, CHM can produce synergistic effects, enhancing the overall intervention and improving patient outcomes.ObjectiveThis study aims to evaluate the efficacy of four CHMs - Xuanbai Chengqi Decoction (XBCQD), Dachengqi Decoction (DCQD), Liangge Powder (LGP), and Fusu Agent (FSA) - in managing ARDS. Using a network meta-analysis (NMA), the study ranks these formulas based on key clinical indicators, including the mechanical ventilation duration (MVD), ICU length of stay (ICU-LOS), and the PaO2/FiO2 ratio (P/F ratio).ResultsA comprehensive literature review identified 18 clinical studies involving 1,134 participants to assess the relative efficacy of the four CHMs. The findings indicated that XBCQD was the most effective in reducing MVD (SUCRA = 87.8%), followed by FSA (64.3%). FSA also demonstrated superior efficacy in shortening ICU-LOS (SUCRA = 73.9%) and improving the P/F ratio (92.2%), with XBCQD ranking second in both outcomes (67.6% and 72.6%, respectively). A significant difference was found between FSA and LGP in improving the P/F ratio (MD = 41.08; 95% CrI: 5.95, 76.22). In contrast, DCQD and LGP ranked lower across most outcomes. Notably, the difference between LGP and placebo in improving oxygenation was not statistically significant (MD = 22.06; 95% CrI: −2.22, 46.35).ConclusionIn combination with Western symptomatic treatments, XBCQD is the most effective intervention for reducing MVD in ARDS patients. FSA demonstrates superior efficacy in improving the P/F ratio and shortening ICU-LOS. However, these findings require further clinical validation to establish their applicability.